Anti-ganglionic acetylcholine receptor antibodies in functional neurological symptom disorder/conversion disorder - Nagata, Ryusei; Matsuura, Eiji; Nozuma, Satoshi; Dozono, Mika; Noguchi, Yutaka; Ando, Masahiro; Hiramatsu, Yu; Kodama, Daisuke; Tanaka, Masakazu; Kubota, Ryuji; Yamakuchi, Munekazu; Higuchi, Yujiro; et al. (Frontiers in Neurology, 2023)
Objective Autoimmune autonomic ganglionopathy (AAG) is a rare disorder characterized by autonomic failure associated with the presence of anti-ganglionic acetylcholine receptor (gAChR) antibodies; however, several studies have reported that individuals with anti-gAChR antibodies present with central nervous system (CNS) symptoms such as impaired consciousness and seizures. In the present study, we investigated whether the presence of serum anti-gAChR antibodies correlated with autonomic symptoms in patients with functional neurological symptom disorder/conversion disorder (FNSD/CD). Methods Clinical data were collected for 59 patients presenting with neurologically unexplained motor and sensory symptoms at the Department of Neurology and Geriatrics between January 2013 and October 2017 and who were ultimately diagnosed with FNSD/CD according to the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition. Correlations between serum anti-gAChR antibodies and clinical symptoms and laboratory data were analyzed. Data analysis was conducted in 2021. Results Of the 59 patients with FNSD/CD, 52 (88.1%) exhibited autonomic disturbances and 16 (27.1%) were positive for serum anti-gAChR antibodies. Cardiovascular autonomic dysfunction, including orthostatic hypotension, was significantly more prevalent (75.0 vs. 34.9%, P = 0.008), whereas involuntary movements were significantly less prevalent (31.3 vs. 69.8%, P = 0.007), among anti-gAChR antibody-positive compared with -negative patients. Anti-gAChR antibody serostatus did not correlate significantly with the frequency of other autonomic, sensory, or motor symptoms analyzed. Conclusions An autoimmune mechanism mediated by anti-gAChR antibodies may be involved in disease etiology in a subgroup of FNSD/CD patients.